Natural resources used in the traditional medicine of the Marinaú community, Caxiuanã forest, Brazil - de Oliveira, Paula Maria Correa; Sousa, João Paulo Barreto; Albernaz, Lorena C.; Salmen Espindola, Laila; Coelho-Ferreira, Márlia (Frontiers in Pharmacology, 2024)
Populations living in Sustainable Use Conservation Units in the Amazon have accumulated knowledge of useful natural resources for their subsistence. We investigated the natural resources used in the community of Marinaú in traditional medicine and assessed the species of interest for bioprospecting or biological conservation. The field study was carried out with 48 informants from the São Sebastião de Marinaú Community, Caxiuanã National Forest (CNF), Brazil, a Sustainable Use Conservation Unit. It involved participant observation, semi-structured interviews, and guided tours. Indices of Use Value (UV), Fidelity Level (FL), and Consensus Factor (ICF) indicated plant species with therapeutic potential. A total of 944 uses associated with 154 plants and 21 animals were reported. The plants are distributed among 59 botanical families and 126 genera. The medicines are prepared mainly by decoction of leaves and bark. According to UV, Veronica (Dalbergia monetaria L.f.) was the most important. The animals used are all vertebrates, and paca (Cuniculus paca) was the most cited. Bile and lard are the parts most used in the recipes. They mentioned 116 diseases, especially those of the digestive system. The ceruzeiro (Allantoma lineata (Mart. ex O.Berg) Miers) had a high consensus of local use, and no additional studies on this species exist. The present study highlighted species in vulnerable conditions and with high agreement in use to treat diseases. Further studies may provide strategies for the sustainable use and conservation of these species and for developing relevant drugs to treat common disorders that affect Amazon populations.